Regular circulation structures in the tropical basin of Mexico City as a consequence of the urban heat island effect - Klaus, Dieter; Jauregui, Ernesto; Poth, Andreas; Stein, Gotthard; Voss, Max (ERDKUNDE, 1999)
During the night and the early morning hours a heat island develops in the central parts of Mexico City. During the late morning and early afternoon hours this heat island migrates to the eastern outskirts of the city as a result of the radiation reduced by air pollution and an oasis effect. The urban heat island effect produces urban winds in the night hours which are reinforced by cold air flows from the mountain ranges surrounding the city. The urban heat island effect produces a convergence. The intensity of the convergence correlates significantly with the intensity of the temperature difference between the central city and the suburbs.